2020
DOI: 10.1001/jamanetworkopen.2020.11127
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Preprint Policies of Top-Ranked Clinical Journals

Abstract: Author Contributions: Ms Massey had full access to all the data in the study and takes responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 5 publications
0
30
0
9
Order By: Relevance
“…53 54 Individual researchers can also increasingly choose to release their research open access through venues such as pre-print servers, like medRxiv, without undermining their ability to publish their findings in peer-reviewed journals. 55 Furthermore, so-called ‘Green Open Access’ policies, where researchers can elect to post peer-reviewed papers in open access repositories, are available for many journals, although most researchers do not use this option. 44 56 57 Scientific publishing is changing and it will be necessary for all stakeholders to adapt.…”
Section: Discussionmentioning
confidence: 99%
“…53 54 Individual researchers can also increasingly choose to release their research open access through venues such as pre-print servers, like medRxiv, without undermining their ability to publish their findings in peer-reviewed journals. 55 Furthermore, so-called ‘Green Open Access’ policies, where researchers can elect to post peer-reviewed papers in open access repositories, are available for many journals, although most researchers do not use this option. 44 56 57 Scientific publishing is changing and it will be necessary for all stakeholders to adapt.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all journals joined ranks and endorsed the use of preprints, including the New England Journal of Medicine and the Lancet. In June 2020, Massey et al 43 from our group led a study of the preprint policies of the 100 top-ranked clinical journals. The study reported that almost 90% explicitly allow preprints.…”
Section: The Ideasmentioning
confidence: 99%
“…The SHERPA/Romeo online resource (https://v2.sherpa.ac.uk/romeo/) was very helpful to facilitate comparison of journal access policies. Most journals allow authors to post a submitted version of a manuscript on a preprint server, 3 although many request that any preprints be updated with the details of subsequent peer reviewed publications. This is important as different digital object identifiers (DOIs) are allocated to the preprint and the published journal paper.…”
Section: Dissemination Via Preprintsmentioning
confidence: 99%